Phytochemicals and Antioxidant Activities in methanol extracts of Endemic Haplophyllum Species from Türkiye - Cennet Yaman (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The aim of the current study is to determine the total flavonoids, phenolics and antioxidant activities of methanol extracts from aerial parts of four endemic Haplophyllum species to Türkiye (H. myrtifolium, H. vulcanicum, H. pumiliforme, and H. sahinii). There are two populations collected from different regions belonging to H. myrtifolium and H. pumiliforme. Antioxidant activities were measured by radical scavenging activity such as the 2, 2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH), and compared with synthetic standards such as trolox, ascorbic acid and butylated hydroxytoluene (BHT). The highest total bioactive contents were recorded as H. sahinii for total phenolic content (66.4 mg GAE/g extract) and H. myrtifolium for total flavonoid content (40.8 mg QE/g extract), but H. vulcanicum displayed the lowest amount for both contents (38.0 mg GAE/g extract and 34.5 mg QE/g extract, respectively). Among the species, H. myrtifolium exhibited the strongest DPPH and ABTS radical scavenging activity followed by H. pumiliforme, H. sahinii and H. vulcanicum. All Haplophyllum species showed higher antioxidant activity for these two radical scavenging activities than trolox and BHT. The phytochemicals and antioxidant activities in methanol extracts from these endemic Haplophyllum species is reported for the first time. The diversity of the findings is to be discussed as likely consequence of the different species and regions.